The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40729-021-00320-3
|View full text |Cite
|
Sign up to set email alerts
|

Does the macro design of an implant affect the accuracy of template-guided implantation? A prospective clinical study

Abstract: Background An implant prosthesis aims to ensure the best possible rehabilitation of function and esthetics following tooth loss. Template-guided insertion is used to achieve an optimal position of the implant with regard to prosthetic restorability, bone availability, and condition of the surrounding soft tissues. The accuracy of template-guided implant placement is subject to various influencing factors. The clinically achievable accuracy depending on the macro design of the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The accuracy was 0.86 mm, 0.76 mm, and 2.49° for tapered implants, 0.94 mm, 0.89 mm, and 2.06° for straight implants, demonstrating that both tapered and straight implants were suitable for dynamic navigation assisted immediate implant placement. This was in accordance with previous studies [18,28] comparing these two approaches under static templates in regular cases.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The accuracy was 0.86 mm, 0.76 mm, and 2.49° for tapered implants, 0.94 mm, 0.89 mm, and 2.06° for straight implants, demonstrating that both tapered and straight implants were suitable for dynamic navigation assisted immediate implant placement. This was in accordance with previous studies [18,28] comparing these two approaches under static templates in regular cases.…”
Section: Discussionsupporting
confidence: 94%
“…Many clinicians tend to choose tapered implants because this macrodesign facilitates implant into the prepared hole [16]. Recently, a model study [17] corroborated tapered implants gained better accuracy than straight implants under static surgical guide, due to the vertically fluted tapered drill design and its influence on osteotomy accuracy, while a clinical trial [18] demonstrated straight implant achieved better accuracy at the entry point. To date, the role of implant macrodesign on accuracy in immediate implant placement has not been clarified so far.…”
Section: Introductionmentioning
confidence: 99%
“…Tapered implants were found to have less platform, apex and angle deviation than the cylindrical ones. In another clinical study, the implant macro design was shown to only affect the vertical deviation at platform implant 26 . All the implants used in this study were of taper design, but there was a variation in the extent of tapering and some macro design elements such as the design of threads.…”
Section: Discussionmentioning
confidence: 74%
“…An in vitro study from El Kholy, Lazarin, et al (2019) found that in sCAIS, tapered implants (BTL) presented higher accuracy compared to parallel wall implants (TL and BL). However, in a recent prospective clinical study, it was found that implant macrodesign (tapered vs. parallel wall) had no influence on the accuracy of fully guided implant placement in any three‐dimensional direction (Schnutenhaus et al, 2021). Even though there is limited evidence in regard to the effect of implant macrodesign in sCAIS, it is worthwhile noting that the majority of the implants analyzed in the present study's control group were BLT placed with relatively shorter distances to the osteotomy bed, which could lead to a possible over‐interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been investigating the effect of different implant macrodesigns and systems in the accuracy of guided implant surgery (El Kholy, Ebenezer, et al, 2019; Schnutenhaus et al, 2021; Yeung et al, 2020). In this study, the overall implant macrodesigns used were BLT (46.3%), TL (37.0%), and BL (16.7%), selected based on the patients’ local soft and hard tissue anatomy.…”
Section: Discussionmentioning
confidence: 99%